Normative Models in Managerial Decision-Making. - Tomkins, Cyril R.; Dominiak, Gere (The Accounting Review, 1977)
Reviews the book "Normative Models in Managerial Decision-Making." by Lawrence A. Gordon, Danny Miller and Henry Mintzberg.